Two dimensional Ti3C2Tx MXene electrode for supercapacitor application - Tuzluca, Fatma Nur; Yesilbag, Yasar Ozkan; Shafiee, Farah Nabilah; Hamidon, Mohd Nizar; Ertugrul, Mehmet (IEEE, 2019)
Two-dimensional materials are one of the most studied materials for many applications in recent years. Among the two-dimensional (2D) metal carbide, MXene is seen as one of the most promising materials for energy storage systems. Among the MXene family, Ti3C2Tx, the lightest material, is one of the electrode materials due to its unique electrochemical performance. In this study, Ti3C2Tx MXene structure was obtained by removing Al layer from Ti3AlC2 MAX structure by selective etching. Exceptional electrochemical performance and high electronic conductivity of Ti3C2Tx was obtained and surface and morphological analyzes were performed with FESEM, EDS, XRD. FESEM has demonstrated that synthesized MXene is a layered solid structure. In addition, synthesized MXene was tested for electrochemical behavior against electrochemical energy storage applications using techniques such as cyclic voltammetry (CV), galvanostatic charge discharge (GCD), and electrochemical impedance spectroscopy (EIS). Characterization and electrochemical tests have shown promising performance in electrochemical charge storage applications.